IMMU-36. THE ROLE OF PD-L1 IN GLIOBLASTOMA-DERIVED EXTRACELLULAR VESICLES IN THE INDUCTION OF IMMUNOSUPPRESSIVE MONOCYTES. (11th November 2019) - Himes, Benjamin; Peterson, Timothy; Tyson, Jasmine; Lee, Helen; deMooij, Tristan; Cumba-Garcia, Luz; Jung, Mi-Yeon; Gustafson, Michael; Dietz, Allan; Johnson, Aaron; Dong, Haidong; Maus, Rachel; et al.
Abstract: Glioblastoma (GBM) is the most common and lethal primary brain tumor, and novel therapeutic strategies that make a substantial impact on outcomes are sorely needed. Immunotherapies have shown great promise in the treatment of a number of cancers in recent year, and a concerted effort is being made to apply these treatment paradigms to GBM. However, many GBM patients exhibit profound immunosuppression, likely limiting the efficacy of such approaches. The mechanisms of this immunosuppression are poorly understood, but tumor-derived extracellular vesicles (EVs), may play a role. We demonstrate that GBM-derived EVs induce the development of myeloid-derived suppressor cells (MDSCs) and non-classical monocytes (NCMs). We further demonstrate that these EV-induced monocytic cells are immunosuppressive, resulting in impaired T cell proliferation upon co-culture. We found that the immunosuppressive effects of tumor-derived EVs appear to be driven by the induction of these immunosuppressive monocytes, as EV treatment of T cells did not significantly impact T cell proliferation. Further, we sought to characterize the important of programmed death ligand 1 (PD-L1) in the induction of these immunosuppressive monocyte populations. We found PD-L1 to be expressed in the EVs from GBM cell lines, and that modulation in PD-L1 expression via either constitutive overexpression or shRNA-mediated knockdown resulted in concordant changes in expression in tumor-derived EVs. We demonstrate that PD-L1 is important for the induction of NCM but not for MDSCs. Taken together, these findings point to a significant role for tumor-derived EVs in the induction of immunosuppressive monocytes in GBM, and that these cells may be a driving force of systemic immunosuppression. PD-L1 is one factor expressed in EVs that has immunomodulatory properties, but additional EV cargo likely plays a major role in the induction of immunosuppressive cells.